Social Index of Educational Effectiveness: A New Approach from the Perspective of Promoting Equity - Leitão, Ulisses Azevedo (Education Policy Analysis Archives, 2015)
In this article, I propose an index, called the Social Index of Educational Effectiveness (SIEE), which allows the establishment of an objective criterion to define the school’s profile concerning the promotion of educational equity. It makes it possible to differentiate schools with an “inclusionary profile,” (SIEE>0), from those with an “exclusionary profile,” (SIEE<0), depending on whether or not the school fosters educational inclusion, and therefore promoting social equity. I have analyzed 272 schools (N=11,732 students) of five urban contexts in Brazil and found behaviors markedly different for the two learning subjects; reading and mathematics, the mean SIEE yielding positive and negative values, respectively. I argue that the SIEE concept is relevant for the analysis of educational effectiveness and should be considered as such by educational researchers and policymakers.